Indigenous Knowledge of Medicinal Plants Used and its Implication towards Health-Seeking Behavior among the Melanau in Pulau Bruit, Sarawak, Malaysia - Dayang Hajyrayati, Awg Kassim; Siti Zaleha, Raduan; Muhammad Wahizul Haswan, Abdul Aziz; Alexander, Chelum; Asrul Asshadi, Mohamad Morni; Rasidah, Abd Wahab (Penerbit Akademia Baru, 2016)
This article presents findings of a survey and an in-depth interview conducted in Pulau Bruit as part of the research project entitled “Traditional health practices and its implication towards health-seeking behavior among the Melanau in Pulau Bruit: Documentation of local heritage”. The aim of the study is to explore health-seeking behavior related to the use of medicinal plant among the Melanau of Pulau Bruit. The survey data and interview reveals factors such as suitability, accessibility, and effectiveness of treatment plays significant roles in determining the health-seeking behavior of the Melanau community of Pulau Bruit. Although the major trend has shown the use of modern and traditional healing practices was combined, a vast majority of the households used medicinal plants totreat minor ailments. The study also reveals that there was a limited transfer of medicinal plants knowledge between generations within the Melanau community of Pulau Bruit. Furthermor, the decline of medicinal plants knowledge for spiritual purposes suggests that it was affected by numbers of external factors such as religion, change of lifestyle and urbanization. A long history of medicinal plants use in traditional health practices also suggests that it may contain therapeutic effects that can be determined by pharmacological analysis.